The Bambuí Health and Aging Study (BHAS): private health plan and medical care utilization by older adults - Maria Fernanda F. Lima-Costa; Henrique L. Guerra; Josélia O. A. Firmo; Pedro G. Vidigal; Elizabeth Uchoa; Sandhi M. Barreto
The aim of this cross sectional study was to investigate whether holding a private health plan affects the consumption of medical services (hospitalization and visits to a doctor) and use of medications by older adults. All residents in Bambuí town (Minas Gerais, Brazil) aged > or = 60 years (n = 1,742) were selected. From these, 92.2% were interviewed and 85.9% were examined (blood tests and physical measurements). After adjustments for counfounders, those under exclusive public coverage (n = 1,296), compared with those holding a private health plan (n = 310), presented some evidence of having worse health status, reported less visits to a doctor, and used a small number of prescribed medications. The main explanation for the aged holding a private health plan was economic, not health. Even though those who had only public health coverage complained more in relation to medical care (70.9%), an important proportion of the aged with a private health care plan presented some kind of complaint (45.2%). Another worrying factor was the difficulty to acquire medication because of financial problems (47.2 and 25.2% reported, respectively). Further investigations are needed to verify whether our results can be generalized to other communities of the country.